WAYS OF IMPROOVING CAR SAFETY IN THE EU TROUGH REGULATION (Perner's Contacts, 2021)
Road safety in the EU has improved significantly over the past decades, thanks to effective action taken at EU and national level to address road user behaviour, vehicles and infrastructure. As a result the EU roads are the safest world-wide. This increased safety can, to a large extent, be attributed to legislative requirements on safety of vehicles that have been introduced to road safety. The EU has, in the past, introduced mandatory fitting of electronic stability control systems on all vehicles and advanced emergency braking systems and lane departure warning systems on trucks and buses, which contribute to the reduction of fatal casualties in traffic by an estimated 5,000 a year. The full potential of these and further active safety technologies can only become reality with large-scale deployment in vehicles on EU roads. The aim of this paper provides a comprehensive overview and proposes a way forward as regards improved vehicle safety for the benefit of all road users, that is to say, all citizens of the European Union.
Keywords: Active Safety, Intelligent Transport Systems, Intelligent Vehicle, Intelligent Vehicle Safety Systems, Passive Safety, Present Vehicle Safety Regulation, Regulation, Vehicle Safety